1995
DOI: 10.1056/nejm199511023331805
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Annual in-Home Comprehensive Geriatric Assessments for Elderly People Living in the Community

Abstract: A program of in-home comprehensive geriatric assessments can delay the development of disability and reduce permanent nursing home stays among elderly people living at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
360
1
7

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 418 publications
(378 citation statements)
references
References 30 publications
10
360
1
7
Order By: Relevance
“…These strategies have been successfully used by others with significant results. [32][33][34][35][36][37] …”
Section: Discussionmentioning
confidence: 99%
“…These strategies have been successfully used by others with significant results. [32][33][34][35][36][37] …”
Section: Discussionmentioning
confidence: 99%
“…In a Dutch RCT, preventive home visits in a general older population showed an increased risk of admission to hospitals among the controls (van Rossum et al 1993). Three other controlled trials found no differences in admission rates between intervention and control groups (Fabacher et al 1994;Stuck et al 1995;Dalby et al 2000). A systematic review and meta-analysis of six studies analysing admission to hospital among the general older population suggested that home visits had no significant effect on hospital admissions (Elkan et al 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Owing to all these evaluations, following benefits can be achieved: prolongation of life span, maintenance and improvement of functional status and quality of life, decrease in hospital and nursing home care, decrease in mortality and hospital costs, and low dependence for activities of daily living (ADL) (9)(10)(11). Advanced age and its adverse effects on mental state and functional capacity must be kept in mind while initiating the therapy, following-up the therapy, or planning alterations of the therapy of diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%